2019
DOI: 10.18821/0869-2084-2019-64-7-417-423
|View full text |Cite
|
Sign up to set email alerts
|

Non-Specific Parameters of Immune Response as a Ring in the Pathogenesis of Remodeling of the Vascular Wall and Destruction of Bone Tissue in Women With Arterial Hypertension in Postmenapus

Abstract: Recently, they increasingly began to pay attention to the role of a nonspecific immune-inflammatory vascular response as a link in general pathogenetic mechanisms with a change in the elastic properties of arteries and phenomena of destructive bone changes, which at the subclinical level is of great importance for the prevention of the development of socially significant diseases. A total of 104 patients were examined (mean age 57.45 years), which were divided into three groups. The first group included 39 hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Our study demonstrated gender-and age-related changes in the metabolome of the intestinal microbiota in patients with AH and abdominal obesity. In our earlier study, we observed a significant increase in the levels of TMA and TMAO, IL-1.6, hs-CRP and GDF15 and a decrease in the levels of SCFA, adiponectin, sex hormones, intestinal hormones and calcium in the presence of multidirectional correlations of biomarkers with PWV and left ventricular hypertrophy [16].…”
Section: Discussionmentioning
confidence: 73%
“…Our study demonstrated gender-and age-related changes in the metabolome of the intestinal microbiota in patients with AH and abdominal obesity. In our earlier study, we observed a significant increase in the levels of TMA and TMAO, IL-1.6, hs-CRP and GDF15 and a decrease in the levels of SCFA, adiponectin, sex hormones, intestinal hormones and calcium in the presence of multidirectional correlations of biomarkers with PWV and left ventricular hypertrophy [16].…”
Section: Discussionmentioning
confidence: 73%
“…These alterations are essential in order to reinforce the arterial tissue against excessive strain and probable dissection [ 7 , 8 ]. Similar examples of remodeling in connective tissues, e.g., bones [ 9 ], are well-documented. This remodeling pathway continues to depose ECM until the source cell is no longer experiencing loads and strains well above the physiological levels.…”
Section: Introductionmentioning
confidence: 87%
“…A recent survey suggests that osteoporosis affects millions of people in the United States, and that most patients are postmenopausal women with low estrogen levels (Patel, 2020). Although the specific pathogenesis of osteoporosis is not fully understood, previous studies have shown that the main causes of osteoporosis are estrogen deficiency and immune inflammatory response (Park et al, 2020; Petelina et al, 2019). In recent years, great progress has been made in studying the relationship between oxidative stress and disease, in which studies have shown that oxidative stress can inhibit the differentiation of osteoblasts and promote the development of osteoporosis (Takanche et al, 2020).…”
Section: Introductionmentioning
confidence: 99%